2019
DOI: 10.1038/s41380-019-0472-7
|View full text |Cite
|
Sign up to set email alerts
|

Autism-like social deficit generated by Dock4 deficiency is rescued by restoration of Rac1 activity and NMDA receptor function

Abstract: Genetic studies of autism spectrum disorder (ASD) have revealed multigene variations that converge on synaptic dysfunction. DOCK4, a gene at 7q31.1 that encodes the Rac1 guanine nucleotide exchange factor Dock4, has been identified as a risk gene for ASD and other neuropsychiatric disorders. However, whether and how Dock4 disruption leads to ASD features through a synaptic mechanism remain unexplored. We generated and characterized a line of Dock4 knockout (KO) mice, which intriguingly displayed a series of AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 65 publications
(80 reference statements)
2
65
0
Order By: Relevance
“…Findings in this study are consistent with the neurodevelopment impairment hypothesis of ASD and dyslexia, in which DOCK4 contributes to a shared genetic factor for both disorders. Using Dock4 knockout mice, we have shown that deficiency of Dock4 in vivo leads to social and communication deficits (Guo et al, 2019). Findings of the current study provide further molecular and cellular evidence that Dock4dependent regulation of neuronal development may underlie the neurobiology basis of social communication and language development.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Findings in this study are consistent with the neurodevelopment impairment hypothesis of ASD and dyslexia, in which DOCK4 contributes to a shared genetic factor for both disorders. Using Dock4 knockout mice, we have shown that deficiency of Dock4 in vivo leads to social and communication deficits (Guo et al, 2019). Findings of the current study provide further molecular and cellular evidence that Dock4dependent regulation of neuronal development may underlie the neurobiology basis of social communication and language development.…”
Section: Discussionsupporting
confidence: 57%
“…Dock4 KO mice (C57BL/6 background) were generated using a standard strategy of Cre-LoxP recombination as previously described (Guo et al, 2019).…”
Section: Dock4 Ko Micementioning
confidence: 99%
See 3 more Smart Citations